Zinc deficiency and its predictive capacity for anemia: Unique model in school children. Issue 8 (10th July 2018) - Atasoy, Halil Ibrahim; Bugdayci, Guler
Abstract: Background: Zinc deficiency is thought to be common in children, but its predictive capacity for anemia is unclear. Thus, this study identified zinc deficiency in school children, and investigated the association between zinc status and hemoglobin, together with other estimates of anemia. Methods: For this case–control study, 349 of 483 children between 6.5 and 14.8 years old were included from primary schools in Bolu, Turkey. We measured weight, length, body mass index, and complete blood count with serum zinc, ferritin, vitamin B12 and folate. We investigated the differences between the groups and the effects of independent predictors such as age, gender, ferritin, zinc, vitamin B12 and folate on hemoglobin, on hierarchical multiple regression analysis. Results: Thirty‐eight (10.9%) of 349 children had low serum zinc concentration, and 21 (6.0%) were anemic. There were 12 anemic children in the zinc‐deficient group and nine in the zinc‐sufficient control group (31.5% vs 2.9%) with similar ferritin levels. On regression analysis, zinc had the strongest association with hemoglobin. On receiver operating characteristic analysis, the cut‐off for serum zinc for prediction of anemia was 71.5 μg/dL. Conclusions: The strongest association of zinc with hemoglobin suggests that low zinc contributed the most to the observed anemia in children.